Numerical and Experimental Investigations of Modal Coherence Characteristics for the Determination of Broadband Noise in Flow Ducts - Xu, Kunbo; Liu, Cunliang; Tong, Fan; Qiao, Weiyang (Frontiers in Energy Research, 2022)
This paper presents a detailed investigation about the modal coherence characteristics of turbomachinery noise. The modal coherence characteristics of ducted noise at high frequencies are investigated by establishing three kinds of ducted sound source distribution models. The results are consistent with the acoustic experimental results of a single-stage axial fan. The results show that acoustic modes of different orders are mutually incoherent, and radial modes within the same circumferential mode have a great degree of coherence. This paper successfully conducted an acoustic measurement on turbomachinery noise by rotating microphone arrays. The acoustic experimental results show that the coherence of some modes has little impact on the measurement of incident acoustic waves in the flow duct, while it leads to about 3 dB deviation in the prediction of the reflected modal sound power and has little influence on the spectral shape of reflected acoustic waves. It was demonstrated that the experimentally measured modal coherence functions give an inner sense of the spatial noise source distribution and enable the investigation of mode scattering within the propagation. Based on the modal coherence characteristics obtained in this paper, more theoretical and methodological studies can be carried out for the turbomachinery broadband noise test.